Plant responses to environmental stimuli : the role of specific forms of plant memory - Thellier, M. (Springer, 2017)
Plants have no sensory organs similar to ours: no eyes, ears or nose. Hence they are often considered to be inert and insensitive. However, they perceive a variety of stimuli such as wind, rain, wounding, cold, drought, attack by pests and herbivores, and even electromagnetic radiations such as those emitted by mobile telephones. Not only they perceive but they also respond to stimuli by modifications in their metabolism and development, sometimes by movements. They have invented the chemical war and the biological war long before us. Some plants would even be able to warn neighbouring plants that herbivores are coming. The responses to stimuli are sometimes immediate and stereotyped. This is the case, for instance, with the folding response of Mimosa leaves and the capture of insects by the carnivorous Dionaea muscipula. However, though lacking a nervous system, plants are also endowed with memory capacity. Upon perception of one or several identical stimuli plants modify the intensity of their response to another occurrence of the same stimulus. In other cases, the perception of a stimulus induces the storage of a piece of information that the plant may repeatedly recall at later times to synchronize its response with other external or internal events (including plant rhythms). So, the stored information may remain latent during lapses of time up to several weeks before being recalled and expressed. What is the evolutionary advantage for plants to possess memory? Where, when and how does the storage of information occur? What is plant memory compared with animal and human memory? Such are the fascinating and stimulating questions that Michel Thellier answers with clarity and scientific rigour. It is indeed a book unique in its kind, which reconsiders our usually accepted ideas while remaining accessible to a broad public fond of Nature, ecology and plant science. Michel Thellier has had a career of professor in plant physiology and biophysics at the University. He has been the Chief Editor of the American journal J. Trace Microprobe Techniques and the Associate Editor of the series "Biology" of the proceedings of the French Academy of Science. He has been the author or editor of a dozen books dealing with plant and cell biology. He is a Member of the French Academy of Science and of the French Academy of Agriculture. All along his career, he has taken a particular interest in plant sensitivity to stimuli. Today, he wishes to help people understand how plant can possess a real capacity of memory, which is, both, so different from ours and so well adapted to the characteristics of its close environment.
Keywords: Plant physiology.; Plant cellular signal transduction.; Plant morphology.; elektronické knihy; electronic books